Gait and Balance Impairment after Acute Methanol Poisoning - Peterová, Kamila; Brožová, Hana; Klempíř, Jiří; Ryšánková, Irena; Bezdicek, Ondřej; Ridzoň, Petr; Vaněčková, Manuela; Zakharov, Sergej; Pelclová, Daniela; Miovský, Michal; Růžička, Evžen (Basic & clinical pharmacology & toxicology, 2018)
Neurological sequelae including gait impairment were reported in survivors after methanol intoxication; however, no systematic study has been published so far. We aimed to analyse gait and balance impairment in a group of Czech methanol poisoning survivors. We examined 43 patients (age 46 ± 13 years) 2-8 months after methanol poisoning and 43 healthy controls. Investigations contained a shortened version of Falls Efficacy Scale (FES), clinical tests of gait and balance including Timed Up and Go test (TUG) and gait analysis using GaitRite® system, neurological and neuropsychological examination, brain imaging, EMG and tests of alcohol consumption. Nineteen patients admitted balance and gait impairment according to FES. Mild to moderate parkinsonian signs showed seven patients. Patients were slower (8.8 versus 5.7 s, p < 0.001) and performed more steps (11.1 versus 7.9, p < 0.001) in TUG compared with the controls. Gait analysis revealed shorter step length (76.5 versus 88.7 cm, p < 0.001), increased double support phase (18.8 versus 15.5%, p < 0.001) and wider base of support (11.3 versus 9.6 cm, p = 0.006) in patients. Eleven patients had deficit of executive function and performed higher cadence compared to the patients with normal execution (122.7 versus 115.0 step/min., p = 0.025). Lower limb polyneuropathy was verified in nine patients, without relation with gait or balance parameters. Neuroimaging revealed lesions mainly in the basal ganglia. Methanol poisoning survivors presented slower wide-based gait with shortened steps corresponding with frontal gait disorder. Higher stepping cadence associated with executive deficit supported the evidence of frontal lobe dysfunction related to impairment of basal ganglia and connections in frontal cortico-basal ganglia loops.
Keywords: nemoci nervového systému; dospělí; methanol; Female; Adult; Gait; ženské pohlaví; Solvents; Nervous System Diseases; Walk Test; neurozobrazování; lidé; test chůzí; Methanol; přežívající; Postural Balance; mozek; rozpouštědla; Male; Aged; Brain; Czech Republic; Česká republika; lidé středního věku; Survivors; senioři; mužské pohlaví; chůze (způsob); Middle Aged; Neuroimaging; posturální rovnováha; Humans